Sea urchin-shaped copper-based catalyst and application thereof in vanillin transfer hydrodeoxygenation reaction

By reducing copper silicate with a sea urchin-like porous structure, the carbon-modified sea urchin-like copper-based catalyst was solved, and the existing catalysts were insufficiently selected and stable in the transfer hydrodeoxygenation reaction, achieving efficient vanillin conversion and selectivity.

CN119897104AActive Publication Date: 2025-04-29ANHUI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510405988.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-04-29
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

Existing transfer hydrodeoxygenation reaction catalysts have challenges in terms of stability and selectivity, especially copper-based catalysts perform poorly and have low selectivity in such reactions.

Method used

Copper silicate with a porous structure of sea urchin is used as the precursor, and the sea urchin-like copper-based catalyst is obtained through reduction, and the performance of the catalyst is further optimized through carbon modification.

Benefits of technology

In the vanillin transfer hydrodeoxygenation reaction, the sea urchin-like copper-based catalyst exhibits conversion and selectivity comparable to the noble metal catalysts and is at a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897104A_ABST
    Figure CN119897104A_ABST
Patent Text Reader

Abstract

The invention discloses a sea urchin-shaped copper-based catalyst and application thereof in vanillin transfer hydrodeoxygenation reaction, and belongs to the technical field of transfer hydrogenation reaction. The technical prejudice that a copper-based catalyst is not suitable for transfer hydrodeoxygenation reaction is broken through, the sea-urchin-shaped copper-based catalyst is obtained by reducing the unconventional sea-urchin-shaped porous structure copper silicate serving as a precursor, and the sea-urchin-shaped copper-based catalyst is proved to have better conversion rate and selectivity in vanillin transfer hydrodeoxygenation reaction; besides, compared with the carbon-modified urchin-shaped porous structure copper silicate serving as a precursor, the carbon-modified urchin-shaped porous structure copper silicate and the reduced urchin-shaped copper-based catalyst have better conversion rate and selectivity, and the catalytic performance of the carbon-modified urchin-shaped copper-based catalyst can be comparable with that of a noble metal catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of transfer hydrogenation reaction, and particularly relates to a sea urchin-shaped copper-based catalyst and application thereof in the transfer hydrogenation deoxygenation reaction of vanillin. Background Art

[0002] Lignocellulosic biomass is one of the important renewable resources. It is a green resource with advantages such as abundant volume and easy access, which can fully meet the world's fuel needs. Biomass pyrolysis oil has low combustion efficiency and insufficient energy conversion rate due to its high oxygen content (20%-50%) and low heat release from combustion of oxygen-containing functional groups such as carboxylic acids and phenols. Hydrodeoxygenation (HDO) is an effective method to reduce the oxygen content in pyrolysis oil.

[0003] Hydrogenation is a general term for reactions in which hydrogen is added to unsaturated compounds (such as alkenes, alkynes, aldehydes, ketones, etc.). This reaction is usually carried out with the help of a catalyst and can convert unsaturated bonds (such as double bonds or triple bonds) into saturated bonds, such as the hydrodeoxygenation reaction of vanillin to vanillyl alcohol. Hydrogenation reactions are mainly divided into two categories: direct hydrogenation and transfer hydrogenation.

[0004] Direct hydrogenation usually involves hydrogen molecules reacting directly with double bonds or functional groups on the reactants. Under the action of the catalyst, the hydrogen molecules are activated and decomposed into hydrogen atoms or hydrogen ions, which then react with organic molecules. Metal catalysts (such as platinum, palladium, nickel, etc.) are usually involved to promote the cracking of hydrogen. Direct hydrogenation requires direct contact and reaction between hydrogen and the substrate. The catalyst usually needs to be activated at high temperature to effectively adsorb and crack hydrogen. It is usually more selective and the reaction conditions (such as temperature, pressure and type of catalyst) can be controlled to selectively hydrogenate specific functional groups or unsaturated bonds.

[0005] Transfer hydrogenation is a hydrogenation reaction that transfers hydrogen atoms or hydrogen ions from a hydrogen source. In this type of reaction, hydrogen does not come directly from hydrogen gas, but from other chemicals (such as alcohols, amines or borohydrides, etc.), and the hydrogen in these chemicals is transferred to the reactants through a catalyst. Since the hydrogen source itself is already a stable hydrogen source and does not require an additional hydrogen supply, transfer hydrogenation can be carried out at room temperature and the reaction conditions are relatively mild, but it also leads to relatively low selectivity of the reaction, and multiple hydrogen sources may be transferred, and the nature of the hydrogen source will affect the reaction selectivity.

[0006] In order to improve the efficiency of transfer hydrodeoxygenation reaction, precious metal catalysts such as palladium Pd, platinum Pt, rhodium Rh, gold Au, etc. are usually selected because precious metals have higher reactivity, can effectively activate hydrogen or hydrogen source, and promote the transfer process of hydrogen atoms. However, precious metals are scarce and the cost of precious metal catalysts is relatively high. In practical applications, there are catalysts using transition metals nickel Ni and cobalt Co, but they are inferior to precious metal catalysts in terms of conversion rate and selectivity.

[0007] Copper-based catalysts refer to catalysts with copper as the main component, which are widely used in a variety of chemical reactions. Copper-based catalysts have become important industrial catalysts due to their relatively low cost, excellent catalytic performance and unique role in certain reactions. It has good catalytic activity and cost advantages, but still faces some challenges in terms of stability and selectivity. Therefore, the catalytic effect on transfer hydrodeoxygenation reaction is also very unsatisfactory and is usually excluded from the list of options. Summary of the invention

[0008] In view of the limitations of existing transfer hydrodeoxygenation reaction catalysts, the present invention proposes a sea urchin-shaped copper-based catalyst, which is not only low in cost, but also has a conversion rate and selectivity comparable to that of precious metal catalysts in the transfer hydrodeoxygenation reaction of vanillin.

[0009] The invention protects a sea urchin-shaped copper-based catalyst, which is obtained by reducing copper silicate with a sea urchin-shaped porous structure.

[0010] As a preferred embodiment of the present invention, the reduction method is to reduce the copper silicate powder with a sea urchin-like porous structure at 450-650° C. using a 10% hydrogen-argon mixed gas to obtain a Cu / SiO2 catalyst.

[0011] As a preferred embodiment of the present invention, the copper silicate with sea urchin-like porous structure is carbon-modified copper silicate.

[0012] As a preferred embodiment of the present invention, the method for preparing copper silicate with sea urchin-like porous structure comprises the following steps: Step 1, synthesizing monodisperse silica microspheres by Stöber method, and uniformly dispersing the silica microspheres in deionized water to form a silica microsphere suspension; Step 2, adding the silica microsphere suspension to a mixed solution containing Cu(NO3)2·3H2O and NH3·H2O, and mixing under magnetic stirring; in the mixed solution containing Cu(NO3)2·3H2O and NH3·H2O, the mass fraction of Cu(NO3)2·3H2O is 0.16%~0.3%, the volume fraction of NH3·H2O is 4%~10%, and the mass ratio of silica microspheres to Cu(NO3)2·3H2O is 13:8~10; Step 3, transferring the mixed solution obtained in step 2 to an autoclave, reacting at a temperature of 120-150° C. for 12-24 hours, centrifuging, filtering, and then washing with distilled water and ethanol to a pH value of 7, and drying to obtain a light blue-green solid powder, which is copper silicate with a sea urchin-like porous structure.

[0013] As a preferred embodiment of the present invention, the method for carbon modification of copper silicate with a sea urchin-like porous structure is to add copper silicate powder with a sea urchin-like porous structure to an ethanol solution containing resorcinol and formaldehyde, then add NH3·H2O, react for 9 to 48 hours under magnetic stirring, centrifuge, filter, and wash multiple times to obtain the carbon-modified copper silicate powder with a sea urchin-like porous structure; In the ethanol solution containing resorcinol and formaldehyde, the mass fraction of resorcinol is 0.11-0.24%, the volume fraction of formaldehyde is 0.20-1.0%, and the added amount of NH3·H2O accounts for 1.2-1.3% of the volume fraction of the ethanol solution.

[0014] As a preferred embodiment of the present invention, the particle size of the selected silica microspheres is 200-500 nm.

[0015] The present invention also protects the use of the above-mentioned sea urchin-shaped copper-based catalyst in the transfer hydrogenation deoxygenation reaction of vanillin. The specific operation is: taking isopropanol, the above-mentioned sea urchin-shaped copper-based catalyst, and vanillin into a high-pressure reactor, then sealing the reactor, and purging the residual air with N2 and then filling it with 2MPa N2, controlling the temperature at 150~180°C, reacting under stirring, and the reaction time is 90~360min, wherein the rotation speed is controlled at 500~900rpm, if the rotation speed is too fast, there will be a problem of liquid splashing, and if the rotation speed is too slow, some silica balls will sink to the bottom and cannot be dispersed; after the reaction is completed, the product liquid and the catalyst are separated.

[0016] The present invention breaks the technical prejudice that copper-based catalysts are not suitable for transfer hydrodeoxygenation reactions, and uses copper silicate with a sea urchin-like porous structure, which is an unconventional copper-based catalyst, as a precursor to reduce a sea urchin-like copper-based catalyst. It has been verified that the sea urchin-like copper-based catalyst has good conversion rate and selectivity in the transfer hydrodeoxygenation reaction of vanillin. In addition, the sea urchin-like copper-based catalyst obtained by reducing the carbon-modified sea urchin-like porous copper silicate as a precursor has better conversion rate and selectivity than the sea urchin-like porous copper silicate that has not been carbon-modified as a precursor, and the catalytic performance is comparable to that of precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the synthesis route of Cu / SiO2-C and Cu / SiO2 catalysts; Figure 2 Schematic diagram of the morphology and fine structure of the Cu / SiO2-C catalyst; Figure 3 Schematic diagram of the morphology and fine structure of the Cu / SiO2 catalyst; FIG4(a) is a graph showing N2 adsorption-desorption isotherms of four Cu / SiO2-C catalysts and Cu / SiO2 catalysts with different carbon contents; Figure 4(b) shows the pore size distribution of four Cu / SiO2-C catalysts and Cu / SiO2 catalysts with different carbon contents; FIG5( a ) is a thermogravimetric graph of the precursors of five catalysts; Figure 5(b) is a thermogravimetric graph of five catalysts; FIG6( a ) is a graph showing the H2-TPR experimental results of copper silicate precursors at different carbon contents; Figure 6(b) is a graph showing the catalytic performance of Cu / SiO2-C catalysts with different carbon contents at 180°C, N2 2MPa, reaction time 300min, and reduction temperature 600°C; Figure 6(c) shows the XRD spectra of Cu / SiO2-C catalysts with different carbon contents at a reduction temperature of 600°C; Figure 6(d) is the TEM image of Cu / SiO2-C catalysts with different carbon contents; Figure 6(e) is a graph showing the catalytic performance of Cu / SiO2-C catalyst with a carbon content of 3.5% at 180°C, N2 2MPa, reaction time of 300min, and different reduction temperatures; Figure 6(f) shows the XRD patterns of Cu / SiO2-C catalyst with 3.5% carbon content at different reduction temperatures; FIG7( a) is an XRD pattern of Cu / SiO2-C catalyst and Cu / SiO2 catalyst; Figure 7(b) is a slow scan XRD pattern of Cu / SiO2-C catalyst and Cu / SiO2 catalyst; Figure 8 (a) is the XPS overall spectra of Cu / SiO2-C catalyst and Cu / SiO2 catalyst; Figure 8(b) is the Cu 2p spectra of Cu / SiO2-C catalyst and Cu / SiO2 catalyst; Figure 9(a) is the Cu LMM Auger spectra of Cu / SiO2-C catalyst and Cu / SiO2 catalyst; FIG9( b ) is a performance diagram of catalytic transfer hydrogenation of vanillin over Cu / SiO2-C catalyst and Cu / SiO2 catalyst; Figure 10(a) is a schematic diagram of the transfer hydrogenation process and products of vanillin; Figure 10(b) is a schematic diagram of the conversion rate and selectivity of the Cu / SiO2-C catalyst over time; Figure 10(c) is a schematic diagram of the conversion rate and selectivity of the Cu / SiO2 catalyst over time; Figure 10(d) is a schematic diagram of the conversion rate of Cu / SiO2 and Cu / SiO2-C catalysts from 90 to 360 min; Figure 10(e) is a schematic diagram of the cycle performance of Cu / SiO2 and Cu / SiO2-C catalysts; Figure 11(a) shows different Cu 0 / + :Cu 2+ XPS graph of Cu / SiO2-C content; Figure 11(b) shows the different Cu 0 / + :Cu 2+ Cu LMM diagram of Cu / SiO2-C content; Figure 11(c) shows the different Cu 0 / + :Cu 2+ XRD spectrum of Cu / SiO2-C content; Figure 11(d) shows Cu 0 :Cu + :Cu 2+ Conversion rate and MMP selectivity of vanillin transfer hydrogenation with different contents at 180℃, N2 2MPa, isopropanol solvent, and reaction time of 5h; Figure 11(e) shows the different Cu 0 / + :Cu 2+ XPS graph of Cu / SiO2 content; FIG12( a ) is a graph showing the H2-TPD experimental results of Cu / SiO2 and Cu / SiO2-C catalysts; Figure 12(b) shows the transfer hydrogenation kinetics of vanillin over Cu / SiO2-C catalyst at different temperatures; Figure 12(c) shows the transfer hydrogenation kinetics of vanillin over Cu / SiO2 catalyst at different temperatures; Figure 12(d) shows the Arrhenius curves of the transfer hydrogenation of vanillin on Cu / SiO2-C and Cu / SiO2; Figure 12(e) is the in-situ Fourier transform infrared spectrum (in-suit FTIR) of vanillin on Cu / SiO2-C catalyst. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0019] Copper silicate (CuSiO3) is a multifunctional inorganic compound. Its unique physical and chemical properties (such as high specific surface area, adjustable pore size, and excellent catalytic activity) make it widely used in many fields. As a catalyst, it is mainly used in NO in motor vehicle exhaust and industrial waste gas. x , CO and VOCs, or industrial wastewater (such as electroplating, mining) containing Pb 2+ 、Cd 2+ 、As 2+ As mentioned in the background technology, copper-based catalysts still face some challenges in terms of stability and selectivity, so the catalytic effect on transfer hydrodeoxygenation reaction is not ideal and is usually excluded from the list of options. Even if copper-based catalysts are applied to transfer hydrodeoxygenation reaction, they usually appear in the form of composite catalysts, and the catalytic effect is far behind that of precious metal catalysts.

[0020] Copper silicate has various forms, including crystalline structure, amorphous state and porous nanostructure. The present invention found that copper silicate with sea urchin-like porous structure (hereinafter referred to as Cu / SiO2 catalyst) has good catalytic performance in the transfer hydrodeoxygenation reaction of vanillin. After further carbon modification analysis experiments (hereinafter referred to as Cu / SiO2-C catalyst), it was found that it has a conversion rate and selectivity comparable to that of precious metal catalysts in the transfer hydrodeoxygenation reaction of vanillin.

[0021] The following is a preparation method of the Cu / SiO2 catalyst and Cu / SiO2-C according to the present invention. Figure 1 Schematic diagram of the synthesis routes of Cu / SiO2-C and Cu / SiO2 catalysts is shown.

[0022] 1. The monodispersed silica microspheres were synthesized by the Stöber method. 0.13 g of silica microspheres were evenly dispersed in 20 mL of deionized water to form a silica microsphere suspension.

[0023] 2. Add the silica microsphere suspension to a mixed solution containing 0.1 g Cu(NO3)2·3H2O and 3 mL NH3·H2O (the solvent is 30 mL deionized water) and mix under magnetic stirring.

[0024] 3. The mixed solution obtained in step 2 was transferred to an autoclave (100 mL) and reacted at 150 °C for 12 h. The mixture was centrifuged and filtered, and then washed with distilled water and ethanol several times until the pH value was 7. After drying, a light blue-green solid powder of copper silicate was obtained, and part of the copper silicate was reserved for later use.

[0025] 4. Take 0.2 g of copper silicate powder and add it to an ethanol solution (ethanol solvent 80 mL) containing 0.0725 g of resorcinol and 0.08 mL of formaldehyde, then add 1 mL of NH3·H2O. React for 9 to 48 h under magnetic stirring, centrifuge, filter, and wash several times to obtain a brown powder, which is the carbon-modified copper silicate.

[0026] 5. The light blue-green solid powder and brown powder were reduced at 450-650 °C for 2 h using a 10% hydrogen-argon mixture to obtain Cu / SiO2 catalyst and Cu / SiO2-C catalyst, respectively.

[0027] The Cu / SiO2 catalyst and Cu / SiO2-C catalyst obtained by the above ratio and reaction conditions have a copper loading of 15wt.%. In addition to the above ratio and reaction conditions, the present invention also tries other ratios and reaction conditions, which are recorded in Table 1. Different formulas and reaction conditions result in different lengths, thicknesses, and core-shell thicknesses of the "thorns" of the growing sea urchins. The clusters shown in Table 1 are also sea urchin-shaped, but they are stuck together, not standard sea urchin-shaped, which will affect the catalytic performance to a certain extent.

[0028] The following discusses the Cu / SiO2 catalyst and Cu / SiO2-C catalyst from the aspects of morphology, geometric structure, electronic structure, and performance in catalytic transfer hydrogenation of vanillin.

[0029] Table 1

[0030] 1. Morphology and structure of Cu / SiO2-C and Cu / SiO2 catalysts The morphology and fine structure of Cu / SiO2-C catalyst and Cu / SiO2 catalyst were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. Figure 2 , 3As shown in the figure. From the SEM and TEM images, we can see that the Cu / SiO2-C catalyst is shaped like a sea urchin, and the thorns on the silica shell are assembled by nanotubes. Element mapping shows that Si, O, C and Cu atoms are evenly dispersed throughout the structure. On the surface of the Cu / SiO2 catalyst, the C element is evenly distributed; on the Cu / SiO2 catalyst and the Cu / SiO2-C catalyst, the Cu element is relatively evenly distributed on the surface.

[0031] By comparison Figure 2 and Figure 3 It can be clearly seen that the urchin-like morphology of the carbon-modified catalyst remains basically unchanged, while the thickness of the carbon-doped amorphous carbon is only about 0.198 nm. In the morphological characterization of the Cu / SiO2-C catalyst, high-resolution transmission electron microscopy (HRTEM) and the corresponding Fourier transform (FFT) images show that the lattice spacing is 0.208 nm, corresponding to the metallic copper (111) plane; at the same time, it can be observed that the particles are not pure metallic copper, but a complex of metallic copper (crystalline) and Cu-O-Si interface (amorphous or low crystallinity). According to the particle size distribution statistics, the average particle size of the Cu / SiO2-C catalyst is 11.97±3.18 nm.

[0032] The Cu / SiO2 catalyst that has not been modified by carbon has obvious metal particles in its SEM and TEM images. The HRTEM image shows that there is obvious Cu2O in the lattice spacing. The average particle size distribution of the Cu / SiO2 catalyst is 17.66±4.58 nm, which is significantly larger than the average particle size of the Cu / SiO2-C catalyst. The HRTEM and corresponding EDS element distribution of the Cu / SiO2 catalyst show that its main structure is Si element.

[0033] Through the analysis of morphology and structure, it can be seen that carbon modification has improved the dispersion of metal particles to a certain extent, and a small amount of carbon modification has not destroyed the basic sea urchin-shaped structure of the catalyst, but has improved the surface microenvironment of the catalyst, thereby improving the performance of the catalyst.

[0034] 2. Geometrical characterization of Cu / SiO2-C and Cu / SiO2 catalysts In order to better explore the effect of carbon modification on the performance of Cu / SiO2-C catalysts, four Cu / SiO2-C catalysts with different carbon contents were prepared. The carbon contents were 2.5%, 2.8%, 3.5% and 4.5%, respectively. The corresponding catalysts were recorded as Cu / SiO2-C-2.5, Cu / SiO2-C-2.8, Cu / SiO2-C-3.5 and Cu / SiO2-C-4.5, respectively.

[0035] Figure 4(a) is the N2 adsorption-desorption isotherms of four Cu / SiO2-C catalysts and Cu / SiO2 catalysts with different carbon contents, and Figure 4(b) is the pore size distribution of four Cu / SiO2-C catalysts and Cu / SiO2 catalysts with different carbon contents.

[0036] Combined with Table 2 (specific surface area and pore volume data of four Cu / SiO2-C catalysts and Cu / SiO2 catalysts with different carbon contents), it can be seen that the adsorption behavior of the catalysts before and after carbon modification has obvious H3-type hysteresis loops generated by mesoporous solids. The curve behavior of these five catalysts is similar. With the increase of single molecule adsorption, micropores exist on the surface. Later, with the increase of pressure, the adsorption amount increases further with multilayer adsorption. Through pore size analysis, the material is mostly micropores (<2nm) and contains a small number of mesopores (2~50nm).

[0037] Table 2

[0038] Combining the specific surface area and pore volume data, it can be seen that the specific surface area of ​​the Cu / SiO2-C catalyst with a carbon content of 2.5-4.5% decreases with the increase of carbon content, from 230.31 m 2 / g decreased to 141.77 m 2 / g; the pore volume first increases with the increase of carbon content (from 0.25 cc / g to 0.35 cc / g), but then decreases significantly after exceeding a certain amount (from 0.35 cc / g to 0.17 cc / g).

[0039] Compared with the Cu / SiO2 catalyst that has not been carbon-modified, the specific surface area and pore volume of the first three groups of Cu / SiO2-C catalysts are improved to a certain extent. However, the fourth group of Cu / SiO2-C catalysts has too much carbon content, which is slightly reduced. This may be due to the post-carbon doping that uses resorcinol and formaldehyde to polymerize to form larger particles of carbon, resulting in the blocking of more mesopores and a decrease in pore volume.

[0040] By combining organic elemental analysis (EA) with thermogravimetric analysis (TG), see Figure 5(a) , 5(b) As shown in the curves, it is obvious that with the increase of carbon doping amount, the weight loss rate increases accordingly. Figure 5(a) is the thermogravimetric curves of the precursors of the five catalysts, and Figure 5(b) is the thermogravimetric curves of the five catalysts.

[0041] Referring to FIG5(a), through the thermogravimetric curves of four carbon-modified copper silicates and copper silicate without carbon modification, the total weight loss rate of copper silicate without carbon modification is 7%, while the total weight loss rate of copper silicate with the highest carbon content is 17%. It can be concluded that as the degree of carbon modification of copper silicate increases, the carbon content increases, the rate of curve descent increases, and the weight loss rate increases.

[0042] As shown in Figure 5(b), in the thermogravimetric curves of the reduced catalysts, Cu / SiO2 without carbon doping, Cu / SiO2-C-2.5 and Cu / SiO2-C-2.8 do not have obvious trapezoidal curves, which is attributed to their low carbon content. When the carbon content increases to more than 3.5%, a weight loss step interval appears; at the same time, as the carbon content increases, the weight loss rate increases accordingly.

[0043] The catalytic performance of the copper silicate precursors of Cu / SiO2-C-2.5, Cu / SiO2-C-2.8, Cu / SiO2-C-3.5, and Cu / SiO2-C-4.5 catalysts is analyzed below. The analysis results refer to Figure 6(a)~6(e) shown.

[0044] As shown in Figure 5(a), a small shoulder peak appears after the carbon content increases to 2.8%, which can be attributed to the small amount of Cu interacting with the support and amorphous carbon. 2+ and Cu + Referring to the H2-TPR experimental results of copper silicate precursors at different carbon contents shown in Figure 6 (a), when the carbon content reaches 4.5%, an obvious small peak is split after 300°C, which can be attributed to the enhanced interaction between carbon and metal.

[0045] The catalytic performance of four Cu / SiO2-C catalysts with different carbon contents was tested at 180℃, N2 2MPa, reaction time 300min, and reduction temperature 600℃, as shown in Figure 6(b). The results show that the catalytic performance of catalysts with different carbon contents is different. At a reduction temperature of 600℃, the conversion rate and MMP selectivity of Cu / SiO2-C-3.5 are the best. The comparison of the conversion rate and selectivity of various vanillin transfer hydrogenation catalysts used in recent years is listed in Table 3. From the comparison of the severity of the reaction conditions, the conversion rate of vanillin and the MMP selectivity, it can be seen that the Cu / SiO2-C catalyst has excellent performance and also has high conversion rate and high selectivity under mild conditions.

[0046] At the same time, it can be seen that the conversion rates of Cu / SiO2-C-2.8 and Cu / SiO2-C-3.5 also reached 100%, which is comparable to the precious metal catalyst 200-Pt / Mo2TiC2 a 、Au / Co3O4 bSimilarly, although the transition metal catalyst Co(H4)@C-HPW also has a 100% conversion rate, the MMP selectivity is only 90%, while Cu / SiO2-C-2.8 can reach 90.24%, and Cu / SiO2-C-3.5 can reach as high as 97.78%. However, in terms of catalyst cost, Cu / SiO2-C is much lower than precious metal catalysts and transition metal catalysts.

[0047] Table 3

[0048] Figure 6(c) shows the XRD spectra of Cu / SiO2-C catalysts with different carbon contents at a reduction temperature of 600°C. It can be seen that with the increase of carbon content, the peak width corresponding to Cu(111) gradually increases. Combined with the TEM characterization of Cu / SiO2-C catalysts with four carbon contents shown in Figure 6(d), it can be seen that carbon modification improves metal dispersion.

[0049] Considering that the catalytic performance of Cu / SiO2-C-3.5 is optimal at a reduction temperature of 600°C, the catalytic performance of Cu / SiO2-C-3.5 catalyst with a carbon content of 3.5% was further tested at different reduction temperatures (450~650°C). The test results are shown in Figure 6 (e), and the corresponding XRD pattern is shown in Figure 6 (f).

[0050] As the reduction temperature increases, the selectivity of MMP is further improved. As shown in Figure 6(f), the increase in calcination reduction temperature gradually reduces the CuO and Cu2O on the surface, which gradually enhances the peak of Cu(111). 0 Combining the previous experiments and literature, we know that Cu 0 The increase in the content is beneficial to the progress of the catalytic transfer hydrogenation reaction of vanillin. From the XRD spectrum shown in Figure 6(f), it can be seen that at the reduction temperature of 600℃ and 650℃, the surface Cu + The Cu2O(111) diffraction peak is basically reduced, but the MMP selectivity of the catalyst at 650℃ is slightly lower than that at 600℃, which can be attributed to the fact that Cu may sinter and agglomerate at too high a temperature, resulting in a decrease in performance. 0 and Cu + Different contents lead to different conversion rates and selectivities, among which selectivity has a greater impact.

[0051] Through the above data analysis, the carbon content of 3.5% is the best carbon content for carbon modification in the present invention. With the increase of carbon content, the temperature range of hydrogen consumption peak of Cu / SiO2-C catalyst becomes wider, and the peak area increases significantly, indicating that the effect of Cu / SiO2-C catalyst, metal and carrier becomes stronger.

[0052] Electronic Structure Characterization of Cu / SiO2-C and Cu / SiO2 Catalysts The Cu / SiO2-C-3.5 catalyst and the Cu / SiO2 catalyst were characterized by means of X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), etc. First, the surfaces of the Cu / SiO2-C-3.5 catalyst and the Cu / SiO2 catalyst were scanned by XRD patterns to obtain the XRD patterns shown in Figure 7(a) and the slow-scan XRD patterns shown in Figure 7(b).

[0053] From the XRD spectra shown in Figure 7(a), we can see that the surfaces of the two catalysts were reduced at 600 °C in H2 / Ar atmosphere. It can be seen that the broad peak at 2θ = 20~30° can be attributed to the mixed phase of SiO2 and C. Peaks are shown at 2θ = 43°, 51°, and 74°, corresponding to the Cu(111), Cu(200), and Cu(220) crystal planes. Therefore, it can be seen that after being reduced at 600 °C in hydrogen and argon, there is no obvious copper oxide on the surface of the catalyst.

[0054] After a detailed slow scan analysis, it can be seen that as shown in Figure 7(b), the carbon-modified catalyst has a slight shift in peak position, from a small angle of 43.51° to 43.37°; at the same time, the peak intensity corresponding to the Cu(111) crystal plane becomes weaker. It can be seen that a small amount of carbon doping is conducive to the dispersion of metallic copper on the catalyst surface, thereby stabilizing the active sites of the catalyst and increasing the effective area of ​​contact with the active sites. This is consistent with the previous TEM image and EDS element distribution map.

[0055] XPS was used to characterize the surface chemical state of the Cu / SiO2-C-3.5 catalyst and the Cu / SiO2 catalyst. Figure 8(a) shows the XPS total spectra of the Cu / SiO2-C-3.5 catalyst and the Cu / SiO2 catalyst, which shows that the catalysts contain Cu, O, C, and Si elements, corresponding to the EDS element distribution diagram. The results show that the catalysts modified by carbonization using the polymerization method of resorcinol and formaldehyde do not introduce other active metal centers; at the same time, it can be seen from the spectrum that the characteristic peak of C in the Cu / SiO2-C-3.5 catalyst is significantly stronger than the characteristic peak of C in the Cu / SiO2 catalyst. Further analysis of the Cu 2p spectrum shows that the characteristic peaks at 932.6 eV and 934.8 eV belong to Cu, respectively. 0 / + and Cu 2+, see Figure 8(b).

[0056] XPS analysis of the elements and valence states of the catalyst, combined with the Cu LMM Auger spectrum shown in Figure 9(a) and the corresponding performance diagram of catalytic transfer hydrogenation of vanillin shown in Figure 9(b), showed that after fitting and peak separation, the Cu valence state content ratio of the Cu / SiO2 catalyst is Cu 0 :Cu + :Cu 2+ = 0.11 : 0.46 : 0.43, while the Cu valence content ratio of Cu / SiO2-C-3.5 catalyst is Cu 0 :Cu + :Cu 2+ = 0.24 : 0.36 : 0.4, the active center Cu that affects the transfer hydrogenation reaction of vanillin 0 / + The content of is significantly increased, indicating that carbon modification can affect the components of electrons in different valence states.

[0057] Study on the Catalytic Transfer Hydrogenation of Vanillin over Cu / SiO2-C and Cu / SiO2 Catalysts The transfer hydrogenation deoxygenation performance test of vanillin was compared for Cu / SiO2-C-3.5 and Cu / SiO2 catalysts. In the transfer hydrogenation reaction with isopropanol as solvent, multiple products were detected, as shown in Figure 10(a). In addition to the target product 2-methoxy-4-methylphenol (MMP), there were two by-products, vanillin alcohol (HMP) and the condensation product 3-methoxy-4-hydroxybenzyl alcohol isopropyl ether (IMP). In the current research on the hydrogenation of vanillin, both HMP and MMP have been reported, but it is easier to directly hydrogenate the aldehyde group to obtain the product vanillin alcohol, so the present invention selects MMP as the target product to study the performance difference between Cu / SiO2-C and Cu / SiO2 catalysts.

[0058] The general catalytic reaction and circulation experiment were carried out in a 25 mL stainless steel high-pressure reactor (Anhui Ke Mi Machinery Technology Co., Ltd.). 30 mg of catalyst and 1 mmol of reactant were added to 10 mL of solvent (isopropanol) and mixed. The mixture was evenly dispersed by ultrasound and transferred to a stainless steel high-pressure reactor; then N2 was passed into the reactor to purge the air several times, and then a certain pressure of N2 was filled, the heating couple was turned on to the target temperature, and the time to maintain this temperature was set. After the reaction was completed, the reactor was cooled to room temperature and filtered with a 0.22 um filter to separate the catalyst and collect the reaction liquid. In the general circulation experiment, the catalyst was separated from the reaction system by centrifugation, washed several times with isopropanol solution, and then used for repeated performance testing.

[0059] The products were identified by gas chromatography-mass spectrometry (GC-MS, Thermo Fisher Scientific-TXQ QuntumXLS), and quantitative analysis was performed using a gas chromatograph (Shimadzu, GC-2010 Plus) equipped with a FID detector and a KB-WAX capillary column (Kromat, USA). Chromatographic analysis method: N2 was used as the carrier gas, the pressure was controlled at 0.1 MPa, the starting temperature was set at 120 °C, the temperature was increased to 240 °C at a rate of 10 °C / min, and maintained for 3 min.

[0060] The catalyst performance before and after carbon modification was tested through basic condition experiments. Figure 10(b) and Figure 10(c) show the changes in conversion rate and selectivity of Cu / SiO2-C-3.5 catalyst and Cu / SiO2 catalyst at 180℃, N22MPa, stirring speed 600 rpm, and reaction time 90-360min, respectively. By comparison, it can be clearly seen that the conversion rate and selectivity of the catalyst after carbon modification are improved.

[0061] After 5-6 hours of reaction, the two catalysts basically reached equilibrium. The unmodified Cu / SiO2 catalyst had an 87% conversion rate and 62% MMP selectivity for vanillin. The carbon-modified Cu / SiO2-C-3.5 catalyst had a 99% conversion rate of vanillin under the same conditions, and the MMP selectivity was further increased to 89%.

[0062] Afterwards, the yield of MMP of the two catalysts at the same reaction time is shown in Figure 10(d), and the cycle stability test diagram is shown in Figure 10(e). As can be seen from Figure 10(d), the conversion rate at the same reaction time is compared with the efficiency of vanillin conversion to MMP at the same reaction time. The performance of the catalyst after carbon modification is significantly higher than that before carbon modification. The conversion frequency and cycle stability of the catalyst after carbon modification are significantly higher than those of the catalyst without carbon modification.

[0063] From the perspective of cycle stability, the Cu / SiO2-C-3.5 catalyst still has an MMP yield of 80% after the fifth cycle, which is a significant improvement in stability compared to the Cu / SiO2 catalyst.

[0064] The following electronic structure analysis verifies the different Cu 0 : Cu + : Cu 2+ The content of the catalyst affects its performance. 0 The main functions are hydrogen activation and surface overflow. Cu 0The nanoparticle surface interacts with the OH or CH bonds of hydrogen donors (such as isopropanol and formic acid) through d-orbital electrons, promoting dehydrogenation to generate active hydrogen species (H*). 0 The isopropanol adsorbed on the surface is oxidized to acetone, releasing hydrogen anions and protons at the same time. The reaction follows the MvK (Mars-van Krevelen) mechanism. 0 The weak adsorption characteristics of unsaturated bonds (C=O, C=C) (through π bond action) reduce the hydrogenation energy barrier and promote selective hydrogenation. In a report in the Journal of Catalysis, a DFT simulation calculation showed that the adsorption energy of the C=O bond on the Cu(111) surface (-1.2 eV) is significantly lower than that of the C=C bond (-0.7 eV), explaining its selective reduction of carbonyl groups. + The role of Cu in the activation of oxygen species and deoxygenation is important. The Chemical Engineering Journal has a statement confirming its participation in deoxygenation. Therefore, the regulation of the valence ratio is an important factor in promoting the multi-step transfer hydrodeoxygenation reaction. While the carbon content of the catalyst is changed by carbon modification, the Cu 0 : Cu + : Cu 2+ Changes in composition structure.

[0065] To further study Cu 0 : Cu + : Cu 2+ The effect of composition variation on Cu was investigated by controlled micro-oxidation of the catalyst in a low oxygen environment. 0 : Cu + : Cu 2+ The composition of the catalyst was adjusted to obtain different contents of Cu / SiO2-C-3.5. Figure 11(a) to Figure 11(e) .

[0066] First, through XPS spectrum analysis, such as Figure 11(a) , 11(e) It can be seen intuitively that under the same trace oxidation, the Cu 2+ The content increase rate of the catalyst was significantly higher than that of the Cu / SiO2-C-3.5 catalyst, indicating that carbon modification helps to improve the interaction between the metal and the carrier.

[0067] Then, the Cu Auger spectrum of Cu shown in Figure 9(a) was used to analyze the Cu 0 and Cu + Analysis of Cu content. 0 As the oxidation time increases, Cu+ , Cu 2+ The content gradually increases. 0 / + : Cu 2+ When the content is 1.49~0.55, the catalytic performance of Cu / SiO2-C-3.5 is maintained at a conversion rate of >99% and a MMP selectivity of more than 95%. 2+ When the content is too high, the performance decreases. At the same time, it can be observed that when only Cu 0 and Cu 2+ or Cu + and Cu 2+ When the catalyst selectivity did not exceed 90%, it means that Cu 0 and Cu + In the catalytic transfer hydrogenation reaction, there is a synergistic effect, which is consistent with the reported literature that Cu 0 -Cu + There is a synergistic effect.

[0068] Through data analysis, Cu 0 : Cu + : Cu 2+ When the content was 22.53:34.47:43, the reaction was carried out at 180 ° C, N2 2MPa, 10mL isopropanol solvent, and 1mmol of vanillin. The catalytic performance of Cu / SiO2-C-3.5 reached a conversion rate of 100% and a MMP selectivity of 97.78%. 0 : Cu + The content is close to 1:1. This verifies that changing the electronic structure of Cu / SiO2-C-3.5 can change the performance of the catalytic transfer hydrogenation reaction, and the Cu can be regulated by carbon modification. 0 : Cu + : Cu 2+ content composition, further refine and improve the performance of the catalyst Cu / SiO2-C-3.5, and promote the CTH process.

[0069] In order to further explore the effect of Cu / SiO2-C-3.5 catalyst on the transfer hydrogenation reaction of vanillin, the temperature-increasing desorption of hydrogen by the catalyst was tested. Figure 12(a) shows the H2-TPD experimental results of Cu / SiO2 and Cu / SiO2-C-3.5. It can be clearly seen that both Cu / SiO2 and Cu / SiO2-C-3.5 catalysts have two desorption peaks. The desorption peak appearing near 300 °C is attributed to the desorption of hydrogen adsorbed by Cu. At the same time, it is obvious that the peak area of ​​Cu / SiO2-C-3.5 after carbon modification increases, which may be due to the increase in surface defects, resulting in an increase in its H2 adsorption amount and an increase in the density of active sites. The latter peak appears at around 450 °C for Cu / SiO2 catalyst, while that for Cu / SiO2-C-3.5 catalyst appears at around 500 °C. The peak position moves toward the high temperature direction, indicating that the adsorption capacity of Cu / SiO2-C-3.5 catalyst is enhanced, the metal dispersion is high, and it is conducive to the transfer hydrogenation reaction.

[0070] In order to further study the evolution of the bonding structure of vanillin on the Cu / SiO2-C-3.5 catalyst, an in-suit FTIR experiment was performed. The in-suit FTIR spectrum is shown in Figure 12(b). As the reaction proceeds, the -1 The peak position of the C=O stretching vibration at 3500cm-1 gradually bends upward, and the peak tends to be flat and basically disappears at 15min. This is partly attributed to the consumption of vanillin and the bond breaking of the aldehyde group of vanillin. After that, the peak at 3500cm-1 -1 The broad peak at 2880cm-1 is OH, which bends from downward to upward, indicating the formation of the intermediate vanillyl alcohol. -1 The -CH3 bending vibration at 1280cm -1 The CO bending vibration at α is strengthened downward, which is attributed to the generation of MMP, and the changes in other signals indicate the adsorption and hydrodeoxygenation processes of vanillin on the Cu / SiO2-C-3.5 catalyst.

[0071] The transfer hydrogenation deoxygenation activity of the Cu / SiO2-C-3.5 catalyst was further explored, and the kinetics of the catalyst were evaluated. Figures 12(c) and (d) show the temperature performance tests of the Cu / SiO2 catalyst and the Cu / SiO2-C-3.5 catalyst, respectively. The test results show that in the range of 150~180°C, the logarithm of the conversion rate of vanillin In (1-conversion of reactant) and the reaction time show a linear correlation through linear fitting, which is consistent with the first-order reaction kinetic characteristics. Through the fitting data, it can be seen that the reaction rate constant increases with the increase of temperature, indicating that increasing the temperature can accelerate the reaction. Both the Cu / SiO2 catalyst and the Cu / SiO2-C-3.5 catalyst conform to the first-order reaction kinetics. At the same time, through the Arrhenius curve and its calculation, the transfer hydrogenation activation energy of the Cu / SiO2 catalyst for vanillin ( E a ) is 45.10 kJ / mol, and the activation energy of Cu / SiO2-C-3.5 catalyst is reduced to 38.92 kJ / mol, indicating that the carbon-modified catalyst Cu / SiO2-C-3.5 has excellent catalytic activity in aldehyde transfer hydrogenation reaction. At the same time, combined with the experimental results of H2-TPD, the reduction in activation energy may be attributed to the fact that carbon modification regulates the electronic composition (Cu 0 : Cu + : Cu 2+ ), to Cu 0 Nearby provides electrons, Cu + The increased content reduces the hydrogen adsorption energy, which reduces the activation energy and improves the catalytic transfer hydrogenation process.

[0072] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention.

Claims

1. A sea urchin-shaped copper-based catalyst, characterized in that The copper-based catalyst is obtained by reducing copper silicate with a sea urchin-like porous structure.

2. The sea urchin-shaped copper-based catalyst according to claim 1, characterized in that The reduction method is to reduce the copper silicate powder with a sea urchin-like porous structure at 450-650°C using a 10% hydrogen-argon mixed gas to obtain a Cu / SiO2 catalyst.

3. The sea urchin-shaped copper-based catalyst according to claim 2, characterized in that The copper silicate with the sea urchin-like porous structure is carbon-modified copper silicate.

4. The sea urchin-shaped copper-based catalyst according to claim 3, characterized in that The method for preparing copper silicate with sea urchin-like porous structure comprises the following steps: Step 1, synthesizing monodisperse silica microspheres by Stöber method, and uniformly dispersing the silica microspheres in deionized water to form a silica microsphere suspension; Step 2, adding the silica microsphere suspension to a mixed solution containing Cu(NO3)2·3H2O and NH3·H2O, and mixing under magnetic stirring; in the mixed solution containing Cu(NO3)2·3H2O and NH3·H2O, the mass fraction of Cu(NO3)2·3H2O is 0.16-0.3%, the volume fraction of NH3·H2O is 4%-10%, and the mass ratio of silica microspheres to Cu(NO3)2·3H2O is 13:8-10; Step 3, transferring the mixed solution obtained in step 2 to an autoclave, reacting at a temperature of 120-150° C. for 12-24 hours, centrifuging, filtering, and then washing with distilled water and ethanol to a pH value of 7, and drying to obtain a light blue-green solid powder, which is copper silicate with a sea urchin-like porous structure.

5. The sea urchin-shaped copper-based catalyst according to claim 4, characterized in that The method for modifying the copper silicate carbon with sea urchin-like porous structure is: The copper silicate powder with a sea urchin-like porous structure is added to an ethanol solution containing resorcinol and formaldehyde, and then NH3·H2O is added, and the mixture is reacted for 9 to 48 hours under magnetic stirring, and then centrifuged, filtered, and washed multiple times to obtain the copper silicate powder with a sea urchin-like porous structure modified with carbon; In the ethanol solution containing resorcinol and formaldehyde, the mass fraction of resorcinol is 0.11-0.24%, the volume fraction of formaldehyde is 0.20-1.0%, and the added amount of NH3·H2O accounts for 1.2-1.3% of the volume fraction of the ethanol solution.

6. The sea urchin-shaped copper-based catalyst according to claim 1, characterized in that The particle size of the selected silica microspheres is 200~500nm.

7. Use of the sea urchin-shaped copper-based catalyst according to any one of claims 1 to 6 in the transfer hydrodeoxygenation reaction of vanillin.

8. The use according to claim 7, characterized in that: Take isopropanol, the catalyst according to any one of claims 1 to 6, and vanillin and add them to a high-pressure reactor, then seal the reactor, purge the residual air with N2 and then fill it with 2MPa N2, control the temperature at 150-180°C, react under stirring, and the reaction time is 90-360 min; after the reaction is completed, separate the product liquid and the catalyst.

Citation Information

Patent Citations

  • Preparation and application of carbon modified silicon dioxide carrier loaded iron-based catalyst for Fischer-Tropsch synthesis

    CN106000404A

  • Application of copper-based catalyst in hydrogenation of 5-hydroxymethylfurfural

    CN109796428A

  • Carbon-modified copper-based catalyst and preparation method and application thereof

    CN111530467A

  • Preparation method of 2-methoxy-4-methylphenol based on selective hydrodeoxygenation of vanillin

    CN114573429A

  • Copper-based catalyst precursor, method for manufacturing same, and hydrogenation method

    US20150224492A1